1995
DOI: 10.1111/j.1432-1033.1995.0266f.x
|View full text |Cite
|
Sign up to set email alerts
|

Separable Binding Sites for the Natural Agonist Endothelin-1 and the Non-Peptide Antagonist Bosentan on Human Endothelin-A Receptors

Abstract: A three-dimensional model for the transmembrane domains of human endothelin-A receptor was built using structural information from bacteriorhodopsin and sequence alignment to other guanine-nucleotide-binding regulatory(G) protein-coupled receptors. Based on this model, 18 amino acids located at the inside of the receptor were mutated and analyzed for binding of the natural ligand endothelin-1 and bosentan, a recently described potent orally active endothelin antagonist [Clozel, M., Breu, V., Gray, G., Kalina, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 32 publications
(12 reference statements)
3
29
1
Order By: Relevance
“…4,5,22 EDN3 is expressed in the first PA in humans, 23 chick, 24 and mice ( Figure S5 and microarray data from the FaceBase Consortium, 25 EDN3. To limit our analysis to the effects resulting from EDNRA signaling, we also included BQ788, an EDNRBspecific antagonist.…”
Section: Genetic Analysesmentioning
confidence: 97%
“…4,5,22 EDN3 is expressed in the first PA in humans, 23 chick, 24 and mice ( Figure S5 and microarray data from the FaceBase Consortium, 25 EDN3. To limit our analysis to the effects resulting from EDNRA signaling, we also included BQ788, an EDNRBspecific antagonist.…”
Section: Genetic Analysesmentioning
confidence: 97%
“…Bosentan, a specific and competitive endothelin receptor (ET A and ET B ) antagonist [660,661], is the first oral drug for the treatment of pulmonary arterial hypertension [662,663]. The absolute oral bioavailability of bosentan in healthy volunteers is 50% and is unaffected by food intake [664].…”
Section: Bosentanmentioning
confidence: 99%
“…Whether also some of the low molecular weight non-peptidergic ET-receptor antagonists are negative allosteric modulators rather than neutral competitive antagonists (De Mey et al, 2011) largely remains to be established. For bosentan, however, it has been shown that its binding site does not fully coincide with that of ET-1 on ET A -receptors (Breu et al, 1995) and ABT-627 was shown to promote internalization of ET A -receptors (Chiou et al, 2000); an effect that is not compatible with neutral competitive antagonism.…”
Section: Discussionmentioning
confidence: 96%